2023
DOI: 10.1073/pnas.2302484120
|View full text |Cite
|
Sign up to set email alerts
|

The competition dynamics of approach and avoidance motivations following interpersonal transgression

Bo Shen,
Yang Chen,
Zhewen He
et al.

Abstract: Two behavioral motivations coexist in transgressors following an interpersonal transgression—approaching and compensating the victim and avoiding the victim. Little is known about how these motivations arise, compete, and drive transgressors’ decisions. The present study adopted a social interaction task to manipulate participants’ (i.e., the transgressor) responsibility for another’s (i.e., the victim) monetary loss and measure the participants’ tradeoff between compensating the victim and avoiding face-to-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…From an evolutionary perspective, uncertainty in the representation of value poses significant challenges for humans and animals in making accurate decisions. The uncertainty of an option’s value is an inevitable aspect of decision-making and is due to various factors like the stochasticity inherited from the environment (Drugowitsch et al, 2016), uncertain reward associations (Daw et al, 2005; Schlichting & Preston, 2016; Shohamy & Wagner, 2008; Wimmer & Shohamy, 2012), stochastic memory retrieval (Bakkour et al, 2019; Shadlen & Shohamy, 2016), imprecise inferential reasoning (Barron et al, 2020; Xue et al, 2024), and/or fluctuating motivational states (Priestley et al, 2024; Shen, Chen, et al, 2023). Our findings regarding early noise illustrate a special case where noise can be effectively managed by the brain circuit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From an evolutionary perspective, uncertainty in the representation of value poses significant challenges for humans and animals in making accurate decisions. The uncertainty of an option’s value is an inevitable aspect of decision-making and is due to various factors like the stochasticity inherited from the environment (Drugowitsch et al, 2016), uncertain reward associations (Daw et al, 2005; Schlichting & Preston, 2016; Shohamy & Wagner, 2008; Wimmer & Shohamy, 2012), stochastic memory retrieval (Bakkour et al, 2019; Shadlen & Shohamy, 2016), imprecise inferential reasoning (Barron et al, 2020; Xue et al, 2024), and/or fluctuating motivational states (Priestley et al, 2024; Shen, Chen, et al, 2023). Our findings regarding early noise illustrate a special case where noise can be effectively managed by the brain circuit.…”
Section: Discussionmentioning
confidence: 99%
“…No contextual effects would be predicted in this case since the rank of input values would always be preserved when scaled by the same constant. This implies a biological substrate where inhibitory neurons, a biological counterpart of the divisive gain-control from the denominator (Louie et al, 2014; Shen, Louie, et al, 2023; Zimmermann et al, 2018), are distinct pools for different options. This motif is supported by recent discoveries of inhibitory neurons with choice-selective properties (Najafi et al, 2020) and implemented in models like the local disinhibition decision model (LDDM) (Shen, Louie, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of the conditions was randomized across participants. Previous studies have demonstrated the validity of this task in inducing different levels of perceived guilt, negative self-conscious emotions, and compensatory behaviors 37 40 , 42 .
Figure 1 Procedure of the interpersonal transgression task and guilt-related measures.
…”
Section: Methodsmentioning
confidence: 99%
“…To characterize how people make social trait judgments from faces, we used naturalistic face stimuli of celebrities of diverse races, face angles, gaze directions, and facial expressions taken in naturalistic contexts (e.g., non-posing photos captured in the street or events) 35 and a set of eight traits that summarize the comprehensive dimensions of trait judgments from faces 36 . To measure recognition of responsibility, guilt experience, and guilt-induced behavioral tendencies following interpersonal transgression, we adopted an interpersonal interaction task where we successfully manipulated participants’ responsibility in causing unpleasant outcomes to a social partner 37 40 . With these two tasks, we tested whether perception of social traits was associated with socio-emotional experience in interpersonal transgression context, and how such association was altered in people with ASD compared to neurotypical participants.…”
Section: Introductionmentioning
confidence: 99%